Facilitating Reading Comprehension for IELTS Through the Use of Principled Explicit Vocabulary Instruction - Tejani, Khadija (2010)
This study investigates the effectiveness of principled explicit vocabulary instruction on the acquisition of vocabulary and the consequent impact on reading comprehension, in preparation for the IELTS. Students at a university in Dubai, United Arab Emirates, on an IELTS preparation course learned lexical items through principled explicit vocabulary instruction. Tests were given that measured vocabulary gains and reading comprehension, before and after instruction. Results of the study indicate that principled explicit vocabulary instruction facilitates the acquisition of new vocabulary, and knowledge of the vocabulary improves reading comprehension. The implementation of principled vocabulary instruction prior to reading comprehension tasks is proposed.